2020
DOI: 10.1080/14616696.2020.1826555
|View full text |Cite
|
Sign up to set email alerts
|

Dying is normal, dying with the coronavirus is not: a sociological analysis of the implicit norms behind the criticism of Swedish ‘exceptionalism’

Abstract: From the outset of the coronavirus crisis, Sweden has been heavyily criticized for its exceptional pandemic mitigation policy. Sweden is often accused pursuing an abnormal and 'disastrous strategy' that puts its citizens' lives at risk. In this article, we analyze the most widespread criticisms of Swedish 'exceptionalism', in order to identify and describe the prevailing implicit norms on which the criticisms are based. While the explicitly proclaimed norms assert that the anti-pandemic measures are aimed at k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It has been suggested that the criticism of the Swedish strategy has been based on the perception that death from coronavirus infection somehow is more harmful to society than death from another infection [ 11 ]. The implicit assumption behind this suggestion is that the pandemic’s mortality rate was not substantially higher than during previous seasonal influenzas and that all-cause excess mortality in Sweden differed significantly from the confirmed coronavirus-related mortality throughout the pandemic wave.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the criticism of the Swedish strategy has been based on the perception that death from coronavirus infection somehow is more harmful to society than death from another infection [ 11 ]. The implicit assumption behind this suggestion is that the pandemic’s mortality rate was not substantially higher than during previous seasonal influenzas and that all-cause excess mortality in Sweden differed significantly from the confirmed coronavirus-related mortality throughout the pandemic wave.…”
Section: Introductionmentioning
confidence: 99%
“…7. The issue of the somewhat privileged status of COVID-19 ill people compared to patients suffering from other diseases is very convincingly elaborated in Grothe-Hammer and Roth (2020). …”
Section: Notesmentioning
confidence: 99%
“…Restabilising is a dire need, as the current situation exports the moral dilemmas onto individuals, who carry them around without the functions to resolve the distinctions to clear moral orders. Posing the question as a distinction between life and death, or even moralising over illegitimate ways to die (Grothe-Hammer and Roth, 2020) in contrast to legitimate ways, demonstrate internal pathways of moral struggle. “Health and education are values that take in all efforts to improve a given situation without resistance–they are values without measure.…”
Section: Meeting At a Moral Crossroadsmentioning
confidence: 99%